Quality PAUD Services Based on a Partnership With Parents in TK Lab School STAI Bani Saleh - Rofiqotul Khusna; Rita Aryani; Novita Deviyanti; Nunuk Marlina; Tine Mulyaningsih (Universitas Panca Sakti Bekasi, 2023)
Service quality can determine the success of PAUD. To realize this, it can be started from quality early childhood services. Quality PAUD services can be influenced by partnerships with parents. The services provided by quality PAUD institutions will generate the trust and loyalty of parents. For this reason, parental satisfaction in partnering can determine the quality of PAUD services. The research objective was to measure the level of parental satisfaction with quality PAUD services received based on a partnership with parents. The method in this research is survey method. The results showed that parental satisfaction in partnering was dominated by indicators of well-facilitated communication between schools and parents compared to other indicators. The conclusion in this study is that quality PAUD services at TK Labschool STAI Bani Saleh based on parental satisfaction in partnering are in the very high category.